Keseimbangan Lintasan Produksi Bis Cap yang Efisien Menggunakan Metode Largest Candidate Rules dan Ranked Positional Weight di PT. P - Crizyela Amelia Rafika Octavia Ledoh; Ni Luh Putu Hariastuti (Fakultas Teknik Universitas Tulang Bawang, 2023)
P Ltd., is a company engaged in the manufacturing industry which produces various technical plastic supporting components with plastic ore as the main raw material. This company produces aircon boxes, bis caps, lamp holders, front grilles, port rings, and bolt-hole masking cups. Some of these items become essential or supplementary components of consumer orders. It employs the Make to Order (MTO) system by making products according to customized products. Of various products produced by P Ltd., a bis cap product was chosen to be the research object for the analysis of its track balance because the bis cap becomes a product that is often ordered by customers and the number of orders is also very large. The high demand of consumers has caused the bis cap production process to get stuck in the quality checking process due to the buildup of finished goods from the production machine. After processing data through the LCR (Largest Candidate Rules) and RPW (Rangked Positional Weight) methods, the optimal results occurred in the LCR method, in which 1 workstation had a line efficiency value of 100.03% and a balance delay value of 0.03%.